Pengaruh Penilaian Kinerja dengan ROI dan EVA terhadap Return Saham pada Perusahaan yang Tergabung dalam Indeks LQ 45 di Bursa Efek Indonesia - Harjono Sunardi (Jurnal Akuntansi, 2010)
There have been many investors who invest funds in certain companies. The purpose of the investment is to obtain the expected stock return. Investors, in investing certainly needs to look at whether the company will be turned into investment activity to perform well or not, because only companies that have good performance that can provide the expected stock return. This research aims to determine the effect of performance appraisal with the ROI and EVA on stock returns. Sampling using purposive sampling techniques, the sample used is a company incorporated in the LQ 45 index with period of August 2008 - January 2009 and not included in the banking sector. This research uses secondary data, secondary data is financial statements in 2006-2007 of companies that were visited in this research. Analytical model used to test the hypothesis is Moderated Regression Analysis. Analysis conducted with the help of SPSS program. The results showed in partial ROI and EVA no effect on stock returns. Simultaneously, ROI and EVA variables also have no effect on stock returns. This is because stock prices are influenced by other factors beyond the company's performance measurement, among other factors of global economic conditions. Key words: Stock return, ROI, EVA, and Performance Measurement